2013
DOI: 10.4103/0973-7847.112832
|View full text |Cite
|
Sign up to set email alerts
|

Exploring scientifically proven herbal aphrodisiacs

Abstract: Procreation was an important moral and religious issue and aphrodisiacs were sought to ensure both male and female potency. Sexual dysfunction is an inability to achieve a normal sexual intercourse, including premature ejaculation, retrograded, retarded or inhibited ejaculation, erectile dysfunction, arousal difficulties (reduced libido), compulsive sexual behavior, orgasmic disorder, and failure of detumescence. The introduction of the first pharmacologically approved remedy for impotence, Viagra (sildenafil)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 48 publications
0
42
0
2
Order By: Relevance
“…An aphrodisiac is defined as a substance (food or drug) that arouses the sexual instinct, induces venereal desire and increases sexual pleasure and performance. Aphrodisiacs can be categorized into three types by their mode of action: libido increasing, sexual pleasure increasing and potency increasing [5]. Aphrodisiacs in recent years have become popular with the increased prevalence of sexual problems worldwide and the incidence of the problem is predicted to rise over 320 million in 2025 globally [6].…”
Section: Introductionmentioning
confidence: 99%
“…An aphrodisiac is defined as a substance (food or drug) that arouses the sexual instinct, induces venereal desire and increases sexual pleasure and performance. Aphrodisiacs can be categorized into three types by their mode of action: libido increasing, sexual pleasure increasing and potency increasing [5]. Aphrodisiacs in recent years have become popular with the increased prevalence of sexual problems worldwide and the incidence of the problem is predicted to rise over 320 million in 2025 globally [6].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants and plant-derived substances have been long term used for treating sexual dysfunction. They can improve libido, sexual potency, and sexual pleasure [12–14]. Anacardium occidentale or Mamuang Himapan in Thai or Cashew, a native plant in Brazil, is widely cultivated in the southern, southeastern, and the eastern parts of Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Malfunction in the glomerular filtration results in the retention of substances, including urea, uric acid and creatinine and this might be responsible for their high serum levels in the treated groups (Selvakumar et al, 2013). Adimoelja and Adaikan (1997) observed no significant differences in Hb levels, in the liver and kidney biomarker enzymes (ALT, AST, Gamma glutamyl transpeptidase, urea and creatinine) before and after TT treatment. In the same direction, Shalan et al (2007) suggested the hepatoprotective effects of vitamins (C, E), Se and silymarin supplements against alcohol intoxication, these antioxidant supplementations significantly reduced the effect of alcohol intake on serum ALT, AST, ALP and LDH activities.…”
Section: Discussionmentioning
confidence: 59%